Proceedings of the 2008 International Conference on Compilers, Architectures and Synthesis for Embedded Systems 2008
DOI: 10.1145/1450095.1450114
|View full text |Cite
|
Sign up to set email alerts
|

Reducing pressure in bounded DBT code caches

Abstract: Dynamic binary translators (DBT) have recently attracted much attention for embedded systems. The effective implementation of DBT in these systems is challenging due to tight constraints on memory and performance. A DBT uses a software-managed code cache to hold blocks of translated code. To minimize overhead, the code cache is usually large so blocks are translated once and never discarded. However, an embedded system may lack the resources for a large code cache. This constraint leads to significant slowdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Strata is configured to form dynamic basic blocks [18], which minimizes code growth (important for embedded systems) [2]. An effectively unbounded code cache is used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strata is configured to form dynamic basic blocks [18], which minimizes code growth (important for embedded systems) [2]. An effectively unbounded code cache is used.…”
Section: Methodsmentioning
confidence: 99%
“…If a fragment does not exist for the application address, the instructions at the address are translated. A 2 The pc register always contains the address of the current instruction + 8.…”
Section: Writes To the Exposed Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…Most DBTs support general-purpose computing platforms. Pin [25], DELI [9] and Strata [1,2,26] are DBTs that support embedded platforms.…”
Section: Related Workmentioning
confidence: 99%
“…We also found that factoring in data structure sizes impacts the relative memory demand of path selection strategies. Previous approaches placed the memory limit on the code cache only [1,2,12,16], leading to inaccurate interpretation of performance results. Additionally, previous work has researched both code selection [10,18,19] and linking strategies [3,6,9,22,25] but from the performance perspective only.…”
Section: Introductionmentioning
confidence: 99%